Spirituality, Entrepreneurship Education and Entrepreneurial Intention Among Moslem Undergraduate Students: Spiritual Well-Being Scaling Application - Buddi Wibowo (School of Business, IPB University (SB-IPB), 2019)
The objectives of this study were to test the effectiveness of entrepreneurship education among Moslem undergraduate students, determinants of intentions, and the interactions between these variables and spirituality that determine the process. Spirituality influences student’s’ view on economic activity and interaction with their environment. The research subjects were Moslem students at the Faculty of Economics and Business of University of Indonesia that may be classified as a nascent entrepreneur: the group that is considering self-employment as a career choice. The techniques of data collection were interviews and questionnaires. The data were analyzed using a quantitative approach of Mann-Whitney U-test to test the effects of education among the groups of students who have received entrepreneurship education and groups that have not, as a control group. The results showed that (1) there are three factors that can identify entrepreneurial intentions which can be identified in detail with three indicators and (2) the effects of entrepreneurship education in shaping the entrepreneurial intentions which depends on student’s’ spirituality.Keywords: entrepreneurship intention, beliefs, education, spirituality